Aneurisma cerebral en paciente adulto mayor - Toalumbo Rodríguez, Karina Maday (2018)
A cerebral aneurysm is a cerebrovascular disease in which there is a dilation of a part of a blood vessel from the brain, which is swelling up in the course of time. The blood pressure increases the risk that the blood vessel is broken and a part of the brain flooded in blood, these can be the product of genetic root alterations or acquired diseases. The risk factors related to unhealthy lifestyle habits are the excessive intake of foods with high levels of fats and sugars, drug abuse, use of certain contraceptives and anticoagulants in addition to chronic diseases such as hypertension, obesity, and, especially atherosclerosis are triggers the onset of brain aneurysms. The present clinical case was carried out in a patient of 63-year-old female who presented the pathology cerebral aneurysm that was detected and treated in an efficient manner. Considering to the nursing of the important professions, in this case analysis one determines the factors of risk that caused the appearance of the pathology, the critical points of the disease and is performed a plan of nursing aimed to improve the life style.